Las especies del género Liolaemus (Liolaemidae). Lista de taxones y comentarios sobre los cambios taxonómicos más recientes - Abdala, Cristian Simón (2021)
Taxonomic lists are important tools for understanding biodiversity and they provide information at diffrent scales about the species distributed within a region; as such, they allow us tounderstand the identities of the species that compose a given supra-specifi taxon. While listsof the species of the genus Liolaemus have been published over the past few decades, providingtaxonomic and systematic information, these lists are now outdated and the number of validspecies within the genus has flctuated rapidly over time and many taxonomic changes havegone unregistered. Although there are alternative means to consult this information, thesesources have suffred from a number of involuntary errors as well as some arbitrary omissionsor inclusions that have affcted the dynamics of species inventories. In this work, we presentthe most complete taxonomic enumeration of the species of Liolaemus to date, including theavailable names for all of the valid and invalid species associated with these taxonomic changes.We recognize a total of 283 valid species in Liolaemus, along with another 64 invalid names.Fiften taxa are recognized as species inquirenda, eight as nomina dubia, and two as nomina nuda.We hope that the careful review of each case and the exhaustive literature review will make thiswork a primary reference on South America's most speciose lizard genus.